If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 2x + -6x Combine like terms: 2x + -6x = -4x 14 = -4x Solving 14 = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 14 + 4x = -4x + 4x Combine like terms: -4x + 4x = 0 14 + 4x = 0 Add '-14' to each side of the equation. 14 + -14 + 4x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = 0 + -14 4x = 0 + -14 Combine like terms: 0 + -14 = -14 4x = -14 Divide each side by '4'. x = -3.5 Simplifying x = -3.5
| 28x^2+28x-96=0 | | 5x+2=2x-102 | | 4x-48=180 | | 8x-19=5x-32 | | 3/8x=69 | | 3L/5=4 | | -1/3(x+5)=6 | | 4(2x+5)=-12 | | (4y^2-6y+7)-(2y^2-6y+3)= | | 5x-15=90 | | 4x+2=-(-x-7) | | n^2+15n+56n= | | x+5-7=1 | | -(-x+12)=6 | | 8/11x=-4/11 | | 8x^2-8x=-2 | | X-8=6x+2 | | -2x+8+4x=15 | | 1.4+(-2g)=-7.2 | | y^2-3y+2.25=0 | | -10(2+x)=60 | | 5-4x-10+2x=17 | | 8-t*3=3(t+2)4 | | 7x+3(-2x-8)=25 | | 17+1.2x=29 | | 9n-15=47 | | -9x-7+6x=-10x-1 | | 5s+60s=11s | | 2x-4x=6 | | 3(2*2)+9(2)= | | 32x-6=0 | | 32-3/8y=6/8y+5 |